Optimization of Disaster Logistics Management by the Karimun Social Affairs Office: Collaboration for an Effective Humanitarian Response - Fauziandi, Ronald; Niko, Nikodemus (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Tanjung Balai Karimun is recognized as a high-risk disaster zone within the Riau Islands Province, with notable vulnerability to both natural and social hazards. These hazards not only result in immediate damage to physical infrastructure and economic systems but also exert a profound impact on the social welfare of the local population. In addressing these multidimensional challenges, the Social Affairs Office of Karimun Regency particularly in the management and distribution of logistical aid to disaster-affected communities. This activity seeks to examine and describe the functions and initiatives of the Social Affairs Office in coordinating logistical support for victims of natural and social disasters in the region. The primary emphasis is placed on understanding how the office operates as a central coordinator to ensure that aid is delivered efficiently, accurately, and in alignment with the specific needs of survivors. The community service program was conducted through direct field engagement, allowing for an in-depth assessment of the aid distribution mechanisms. Findings indicate that the Social Affairs Office assumes a central position in coordinating the provision of essential resources, including food supplies, medical assistance, and psychosocial support. Nevertheless, several operational challenges persist—chief among them being delays in aid shipments from the Ministry of Social Affairs, which significantly hinder the timeliness of emergency response efforts and compromise the ability to address the immediate needs of affected populations.